2016
DOI: 10.1080/09593330.2016.1166267
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the efficiency of a mixed culture biofilm for the treatment of black liquor and molasses in a mediator-less microbial fuel cell

Abstract: A microbial fuel cell (MFC) is an emerging environment-friendly technology to recover the useful energy available in waste by using microorganisms as catalyst. In this study, double chamber mediator-less MFCs separated by proton exchange membrane (PEM; Nafion) were constructed to determine the efficiency of mixed culture in using complex substrates (molasses and black liquor). It was found that activated sludge can serve as efficient source of electricigens for biofilm development on an anode. Power density of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…A study was conducted to evaluate the efficiency of a double chamber MFC using complex substrates such as molasses and black liquor [ 35 ]. The study showed the positive effect of activated sludge by increasing the efficiency of electrogenic bacteria.…”
Section: Complex Substratesmentioning
confidence: 99%
See 2 more Smart Citations
“…A study was conducted to evaluate the efficiency of a double chamber MFC using complex substrates such as molasses and black liquor [ 35 ]. The study showed the positive effect of activated sludge by increasing the efficiency of electrogenic bacteria.…”
Section: Complex Substratesmentioning
confidence: 99%
“…Efficiency parameters such as PD max of 2.425 W m −2 and COD removal of 67% were observed with molasses, whereas PD max of 3.55 W m −2 and COD removal of 78% were observed with black liquor. Increasing the surface area of the PEM increased the voltage generated by 5–8 times [ 35 ]. Similarly, a dual-chamber MFCs performance was evaluated using simulated molasses wastewater, with MnO 2 as the cathode catalyst for carbon cloth cathode or carbon felt cathode [ 51 ].…”
Section: Complex Substratesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore controlling methanogens in MFCs is an important operational parameter to ensure that the substrate is consumed during power production. Full-strength molasses wastewater (130,000mg COD/L) was used in a two-chamber MFC (Ali et al, 2016). The cell achieved 67% COD removal and produced a maximum power density of 242 mW/m 3 .…”
Section: Sugar-based and Distillery Wastewatermentioning
confidence: 99%
“…Subsequently, an electron is conducted towards cathode in order to directly convert chemical energy into electrical energy achieving wastewater treatment. Protons on the other side are transported to the cathode chamber through a proton conducting material like Nafi on membrane (3) or salt bridge where it combines with the electron and oxygen to form water using diff erent biological or chemical catalysts (4,5).…”
Section: Introductionmentioning
confidence: 99%